2011
DOI: 10.1038/onc.2010.603
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Akt/mTOR pathway in Brca1-deficient cancers

Abstract: The breast cancer susceptibility gene 1 (Brca1) has a key role in both hereditary and sporadic mammary tumorigenesis. However, the reasons why Brca1-deficiency leads to the development of cancer are not clearly understood. Activation of Akt kinase is one of the most common molecular alterations associated with human malignancy. Increased Akt kinase activity has been reported in most breast cancers. We previously found that downregulation of Brca1 expression or mutations of the Brca1 gene activate the Akt oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 40 publications
(60 reference statements)
4
47
1
Order By: Relevance
“…68 This is consistent with our model of DNA damage-associated pAKT-S473, since BRCA1-associated tumors show high levels of genomic instability. Furthermore, Xiang and colleagues demonstrated that the increase in pAKT-S473 in BRCA1-deficient tumors was not associated with oncogenic mutations in PIK3CA, which further supports our model of PI3K-independent pAKT-S473 phosphorylation in response to DNA damage.…”
Section: Note Added In Proofsupporting
confidence: 78%
“…68 This is consistent with our model of DNA damage-associated pAKT-S473, since BRCA1-associated tumors show high levels of genomic instability. Furthermore, Xiang and colleagues demonstrated that the increase in pAKT-S473 in BRCA1-deficient tumors was not associated with oncogenic mutations in PIK3CA, which further supports our model of PI3K-independent pAKT-S473 phosphorylation in response to DNA damage.…”
Section: Note Added In Proofsupporting
confidence: 78%
“…Further study by Kao et al [23] demonstrated that overexpression of PTEN resulted in decreased Akt1 phosphorylation and repair of DNA-DSB. This study does not support a role for increased Akt activity in hampering HR, as has been suggested by others [192][193][194]. However, if Akt activity leads to inhibiting HR, because DNA-DSB repair involves both the NHEJ and HR repair pathways, the negative effect of Akt on HR might be dominated by Akt-mediated stimulation of NHEJ.…”
Section: Control Of Dna Damage By Akt As An Important Mechanism For Rcontrasting
confidence: 41%
“…HR deficiency is associated with increased phosphorylation of Akt1 at S743, as shown in breast cancer patients. Likewise, tumor formation due to BRCA1 deficiency is reduced by Akt1 depletion [192]. Inhibition of HR by Akt1 activity in BRCA1-proficient breast cancer cells has been demonstrated to be due to the induction of cytoplasmic retention of BRCA1 and RAD51 [193].…”
Section: Control Of Dna Damage By Akt As An Important Mechanism For Rmentioning
confidence: 98%
“…It has already been shown that AKT could be inactivated by BRCA1 [4], [36]. This major oncoprotein can induce glycolysis via multiple mechanisms, including expression and activation of hexokinases (AKT can phosphorylate HK2) and activation of PFK enzymes [29].…”
Section: Discussionmentioning
confidence: 99%